2019
DOI: 10.1186/s13005-019-0195-7
|View full text |Cite|
|
Sign up to set email alerts
|

The tablet computer’s impact on learning and National Dental Examination scores in orthodontics - a mixed-method research

Abstract: Background To assess the educational impact of a one-to-one tablet PC (TPC) program by analysing university students’ learning skills and related scores of the National Dental Examination (NDE) in Germany. Methods The study design was a mixed-method approach consisting of a survey and a comparison of NDE scores. Students received a loaned non-preloaded and non-managed TPC during three consecutive orthodontic semesters. Usability and learning benefits in clinical and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Estudos demonstram um resultado positivo sobre o uso das ferramentas digitais na percepção dos alunos, já que maioria deles considerou que o uso de dispositivos móveis e aplicativos de aprendizagem nos cursos de Odontologia era útil e que suas atitudes em relação a aprendizagem móvel eram positivas (Rung, Warnke & Mattheos, 2014;Stamm, et al 2019). Em concordância Mergany, Dafalla e Awooda (2021) indica que os alunos acreditam nas novas oportunidades de aprendizagem obtidas a partir dessa metodologia, contribuindo para a educação moderna em saúde, aumentando assim seu desempenho acadêmico.…”
Section: Fonte: Autores (2021)unclassified
“…Estudos demonstram um resultado positivo sobre o uso das ferramentas digitais na percepção dos alunos, já que maioria deles considerou que o uso de dispositivos móveis e aplicativos de aprendizagem nos cursos de Odontologia era útil e que suas atitudes em relação a aprendizagem móvel eram positivas (Rung, Warnke & Mattheos, 2014;Stamm, et al 2019). Em concordância Mergany, Dafalla e Awooda (2021) indica que os alunos acreditam nas novas oportunidades de aprendizagem obtidas a partir dessa metodologia, contribuindo para a educação moderna em saúde, aumentando assim seu desempenho acadêmico.…”
Section: Fonte: Autores (2021)unclassified
“…A study of nursing college students in Korea, Vietnam, and Mongolia [ 15 ] also showed that CBTs were cost-effective and convenient. Meanwhile, a study [ 20 ] of medical students in Germany showed that tablet-computer-based learning significantly improved students’ grades. In the case of the United States, a study of CBT was conducted targeting college [ 21 ], dental college [ 12 ], and pharmaceutical college students [ 22 ].…”
Section: Introductionmentioning
confidence: 99%